EFFECTIVENESS OF ECONOMIC REFORMS AND IMPROVING THE INVESTMENT ENVIRONMENT IN UZBEKISTAN - Ikramova Shakhnoza Odilovna (European Science Publishing, 2024)
The article analyzes the main aspects of increasing the effectiveness of economic reforms and improving the investment climate in Uzbekistan. The achievements and prospects for creating a stable and competitive economy, as well as the problems facing the country, will be considered. The main attention was paid to attracting investments, modernizing infrastructure, and introducing innovative approaches to economic management. The work provides a theoretical understanding of the process of economic transformation and the possibilities for its successful continuation.
Keywords: Economic reforms, investment climate, Uzbekistan, efficiency, innovation, modernization, sustainable development.